The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.physa.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical pairwise entanglement and two-point correlations in the three-ligand spin-star structure

Abstract: We consider the three-ligand spin-star structure through homogeneous Heisenberg interactions (XXX-3LSSS) in the framework of dynamical pairwise entanglement. It is shown that the time evolution of the central qubit "one-particle" state (COPS) results in the generation of quantum W states at periodical time instants. On the contrary, W states cannot be generated from the time evolution of a ligand "one-particle" state (LOPS). We also investigate the dynamical behavior of two-point quantum correlations as well a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Above all, the generation of W states is the primary condition of such captivating applications. From dynamical point of view, the quantum W states can be generated via evolution of an initial quantum state either in a spin chain [10] or in a spin star network [18]. It may be interesting that, opposing to spin chains through which W states can be dynamically created by four qubits at the most [10], star networks have shown that such states can be generated by the same number of qubits at least [18].…”
Section: Introductionmentioning
confidence: 99%
“…Above all, the generation of W states is the primary condition of such captivating applications. From dynamical point of view, the quantum W states can be generated via evolution of an initial quantum state either in a spin chain [10] or in a spin star network [18]. It may be interesting that, opposing to spin chains through which W states can be dynamically created by four qubits at the most [10], star networks have shown that such states can be generated by the same number of qubits at least [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile to remark, moreover, that the quantum Heisenberg spin star is not just a theoretical curiosity without any connection to a real-world system, but it has a variety of experimental realizations in tetranuclear molecular complexes such as CrNi [ 17 , 18 ], CrMn [ 19 ], Cu , Ni and NiCu [ 20 ]. From the perspective of quantum entanglement, only static and dynamic pairwise entanglement, two-point correlations and quantum discord of the spin-1/2 Heisenberg star with the exchange and Dzyaloshinskii–Moriya anisotropies were explored in detail in zero magnetic field and the absence of the exchange interaction between the peripheral spins [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Above all, the generation of W states is the primary condition of such captivating applications. From dynamical point of view, the quantum W states can be generated via evolution of an initial quantum state either in a spin chain [10] or in a spin star network [18]. It may be interesting that, opposing to spin chains through which W states can be dynamically created by four qubits at the most [10], star networks have shown that such states can be generated by the same number of qubits at the least [18].…”
Section: Introductionmentioning
confidence: 99%